The making of lawyers' careers inequality and opportunity in the American legal profession - Nelson, Robert L. 1952–; Dawe, Meghan; Garth, Bryant G.; Michelson, Ethan; Wilkins, David B.; Dinovitzer, Ronit 1971–; Sterling, Joyce Sheila 1945– (Chicago The University of Chicago Press, 2023)
"How do hierarchies of race, class, gender, and law school status condition the career trajectories of lawyers? And how do individual lawyers strategically navigate the constraints and opportunities of their environments? Where do they find professional satisfaction? This book offers an unprecedented account of opportunity structures and social stratification within the early 21st century American legal profession, combining unique longitudinal survey data with interviews, storytelling, and insights from social theory. Starting in 2000, the authors collected over 10,000 survey responses from more than 5,000 lawyers, following these lawyers through the first twenty years of their careers. They also conducted in-depth interviews with more than 200 lawyers. They contextualize their findings through attention to the features of a market-driven legal profession, in particular the growth in recent decades of the private sector relative to the public sector and corresponding disparities in earnings and status between these different segments. The analysis in this book reveals a legal profession that is highly stratified. Although individual lawyers exercise agency and often find satisfaction in their work, there are deep divisions within the profession by client type and practice setting, and women and attorneys of color face discrimination and persistent barriers to advancement. The careers of lawyers both reflect and reproduce inequalities in law and society writ large"--
Part I. Introduction. Introduction : the making of lawyers' careers; From the golden age to the age of disruption : setting the context for lawyers' careers in the new millennium-- Part 2. The structure of lawyers' careers. Change and continuity in the legal field : from walled-off hemispheres to more or less mixed hierarchical sequences; Race, class, and gender in the structuring of lawyers' early careers; Two hemispheres revisited : fields of law, practice settings, and client types-- Part 3. The narratives of lawyers' careers. Moving up and moving on : careers in law firms; Rethinking the solo practitioner; Moving inside : practicing law in business organizations; Commitment, careerism, and stratification : careers in government, nonprofits, and public interest organizations-- Part 4. Inequalities of race and gender. White spaces : the enduring racialization of American law firms / with Vitor M. Dias -- Student debt and cumulative (dis)advantage in lawyers' careers; Hegemonic masculinity, parenthood, and gender inequality / with Andrea Mogosanu-- Part 5. Public roles and private lives. Dualities of politics, public service, and pro bono in lawyers' careers / with Ioana Sendroiu-- Lawyer's satisfaction and the making of lawyers' careers / with Ioana Sendroiu-- Conclusion. Conclusion : structure and agency in the making of lawyers' careers.
Includes bibliographical references (pages 369-393) and index.
Keywords: Equality before the law; Lawyers; Practice of law; Discrimination in employment -- Law and legislation; Law -- Vocational guidance